HUKUM INTERNASIONAL DIDALAM MASYARAKAT DAN PERMASALAHAN WILAYAH ANTARNEGARA - I Nyoman Tegar Seputra; Ni Putu Rai Yuliartini; Komang Febrinayanti Dantes (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This paper examines international law and the territory between countries. International law was born because of the existence of an international community so that this became the basis for the formation of international law. The international community is used as a sociological foundation in shaping international law. International relations arise because of a factor that requires each other from one country to another in various interests. The territory of the state is part of one element that has a very important meaning. According to international law, the territory of a state consists of land, sea and air. A country's territory will be said to be a permanent territory if it has definite boundaries. State boundaries are something that is very valuable and important in order to clarify or show the boundaries of the country's sovereignty to be implemented. In this case, there will be territorial boundary problems between countries. According to international law, there are several ways of settlement in the form of a peaceful settlement and a forced or violent settlement.